Which Maturation Indicator is Most Accurate in Predicting Cessation of Facial Growth? A Systematic Review of the Literature. Issue 3 (5th May 2022) - Reategui, Alvaro; Phillips, Sarah; Khetpal, Sumun; Parsaei, Yassmin; Funaro, Melissa; Mukherjee, Thayer; Lopez, Joseph; Steinbacher, Derek M.
Abstract : Purpose: The determination of facial growth maturity is crucial before surgical intervention in pediatric patients. To the author's knowledge, there are several indicators of skeletal maturity, but there remains a lack of consensus regarding their application when determining surgical timing. The purpose of this study was to determine the most accurate skeletal maturity indicator in predicting facial growth maturation. Materials and Methods: A systematic review was done to determine the most predictive indicator for facial growth maturity. We hypothesized that menses' onset was the most predictive of these maturity indicators. This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. A systematic search of MEDLINE, Cochrane, Embase, Scopus databases, and Google Scholar, was done in October 2020 to identify citations related to maturity indicators assessing craniofacial growth. The quality of evidence was determined using the Joanna Briggs Institute Critical Appraisal Checklist for Cohort Studies. Results: Of the 13, 289 articles screened, 1 retrospective and 1 prospective study met inclusion criteria. No articles were identified that provided evidence for our hypothesis. Based on the 2 included studies, it was concluded that a handwrist x-ray was more predictive of facial growth cessation (compared to other skeletal maturity indicators). Conclusions: Based on the literature, handwrist radiography serves as the most predictive method in determining the facial growth maturity. The paucity of articles within this investigation highlights the need for greater research efforts to investigate the predictability of indicators to evaluate facial growth maturation. PROSPERO registration number: CRD42020207388